2019
DOI: 10.3390/ijms21010284
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Mushroom Treatment in Meniere’s Disease with Coriolus versicolor: A Rationale for Therapeutic Intervention in Neuroinflammation and Antineurodegeneration

Abstract: Meniere’s disease (MD) represents a clinical syndrome characterized by episodes of spontaneous vertigo, associated with fluctuating, low to medium frequencies sensorineural hearing loss (SNHL), tinnitus, and aural fullness affecting one or both ears. To date, the cause of MD remains substantially unknown, despite increasing evidence suggesting that oxidative stress and neuroinflammation may be central to the development of endolymphatic hydrops and consequent otholitic degeneration and displacement in the reun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 74 publications
0
35
0
Order By: Relevance
“…Nrf2, one of the most important transcription factors that activates several genes with cytoprotective function, participates in antioxidant and anti-inflammatory reactions [ 72 , 73 , 74 , 75 , 76 , 77 ]. These cytoprotective genes encode a wide variety of phase II detoxification enzymes, such as NAD (P) H: quinone oxidoreductase 1 (NQO1), HO-1, γ-GCS, glutathione S-transferase (GST) and glutamate-cysteine ligase, thioredoxin, thioredoxin reductase, thermal shock proteins and many others [ 31 , 78 , 79 , 80 , 81 ]. Cell culture studies have shown that HT was the only olive oil phenol capable of increasing the transactivation of Nrf2, which suggests that this polyphenol could be responsible for the induction of Nrf2-dependent gene expression [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2, one of the most important transcription factors that activates several genes with cytoprotective function, participates in antioxidant and anti-inflammatory reactions [ 72 , 73 , 74 , 75 , 76 , 77 ]. These cytoprotective genes encode a wide variety of phase II detoxification enzymes, such as NAD (P) H: quinone oxidoreductase 1 (NQO1), HO-1, γ-GCS, glutathione S-transferase (GST) and glutamate-cysteine ligase, thioredoxin, thioredoxin reductase, thermal shock proteins and many others [ 31 , 78 , 79 , 80 , 81 ]. Cell culture studies have shown that HT was the only olive oil phenol capable of increasing the transactivation of Nrf2, which suggests that this polyphenol could be responsible for the induction of Nrf2-dependent gene expression [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…These effects represent a powerful instrument supporting redox homeostasis under stressful conditions [111] and support the assumptions that the helpful properties of polyphenols carry out through adaptive stress response vitagenes. Within this context, both heme oxygenase-1 (HO-1) and Hsp70 have received considerable attention for their recognized antioxidative function needed to maintain cell homeostasis [112]. Moreover, the well-known principle of hormesis may be applied also to HO-1.…”
Section: Redox Homeostasis and The Inflammatory Responsementioning
confidence: 99%
“…curcumin, resveratrol, flavonols present in Ginkgo biloba extracts, polyphenols present abundantly in the leaves and in the ripening fruits of the olive tree, Olea europaea ), as well as mushrooms ( Hericium Erinaceus , Coriolus versicolor ) can significantly modulate Nrf2 and Nrf2-dependent vitagenes expression, showing neuroprotective action. This can potentially resolve pathologies such as AD, PD and also Meniere’s Disease, another degenerative pathology ( Amara et al, 2020 , Trovato et al, 2016a , Trovato et al, 2016b , Trovato Salinaro et al, 2018 , Scuto et al, 2019 ).…”
Section: Molecular Mechanisms Involving Ozone (O 3 mentioning
confidence: 99%
“…Preconditioning is a process whereby an initial low dose of a stressor agent upregulates adaptive mechanisms that enhance resilience against subsequent and acute stressor agents within a time-sensitive window of ∼ 10–14 days ( Calabrese, 2016 ). Different studies demonstrated that the supplementation with Coriolus versicolor ( Ferreiro et al, 2018 , Scuto et al, 2019 , Trovato Salinaro et al, 2018 , Trovato et al, 2016a ), and Hericium Herinaceus ( Trovato Salinaro et al, 2018 , Trovato et al, 2016b ) biomass and polyphenols ( Mao et al, 2019 ) can maintain the response to neutralize intracellular pro-oxidant/neuroinflammatory status, preventing different neurological conditions.…”
Section: Effect Of Ozone Oxidative Preconditioning On Oxidative Stresmentioning
confidence: 99%